2022
DOI: 10.1007/s40123-022-00590-z
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Risk Factors for Dry Eye After Pediatric Strabismus Surgery

Abstract: Introduction This study aimed to investigate the incidence and risk factors for dry eye after pediatric strabismus surgery. Methods Children aged 5–12 years who underwent strabismus surgery were included in this single-center, prospective, cohort study. The ocular surface assessments were conducted 1 day before and 1, 4, and 8 weeks after surgery. The main outcome measures were the incidence of dry eye after strabismus surgery and associated risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…When the visual organ is diseased, it will affect the function of the eyeball, optic nerve and brain, resulting in the inability to perform normal visual activities [ 37 ]. Current studies have shown that Internet addiction may cause eye fatigue, dry eye, myopia, and other problems [ 38 , 39 ]. Nevertheless, the visual function parameters and visual physiological indicators of addicts are not significantly different from those of ordinary people, and the visual organs do not appear as apparent lesions so that they can carry out normal visual activities [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the visual organ is diseased, it will affect the function of the eyeball, optic nerve and brain, resulting in the inability to perform normal visual activities [ 37 ]. Current studies have shown that Internet addiction may cause eye fatigue, dry eye, myopia, and other problems [ 38 , 39 ]. Nevertheless, the visual function parameters and visual physiological indicators of addicts are not significantly different from those of ordinary people, and the visual organs do not appear as apparent lesions so that they can carry out normal visual activities [ 40 ].…”
Section: Discussionmentioning
confidence: 99%